Potential of Flavonoid Compounds from Rhodomyrtus tomentosa as Anticholesterol: An In Silico Study - Lumbantoruan, Lamtiur; Sinaga, Ernawati; Simanjuntak, Kristina; Nurbaya, Siti; Prasasty, Vivitri Dewi (Universitas Nasional Jakarta, 2024)
Indonesia's biodiversity ranks second largest in the world. This vast potential, if managed well, can be utilized as raw materials for medicines. Currently, 96% of drug raw materials in Indonesia are still imported, making medicines expensive. Therefore, efforts are needed to achieve self-sufficiency in drug raw materials, including researching Indonesian plants with potential as hypercholesterolemia drugs to be used as native raw materials. This study aims to determine the potential of flavonoid compounds in Rhodomyrtus tomentosa fruit as an alternative hypercholesterolemia drug. Six flavonoids were identified: myricetin, quercetin, quercetin 7,4'-diglucoside, dihydromyricetin, kaempferol, and vitexin in R. tomentosa (Karamunting) fruit. The method used was an in silico study. In silico studies are used to screen compounds based on their mechanism of action against target proteins. In this study, myricetin, quercetin, dihydromyricetin, kaempferol, quercetin 7,4'-diglucoside, and vitexin were subjected to molecular docking using Autodock Vina software to determine the affinity and interaction of these six compounds with the HMG-CoA reductase enzyme, which acts as an intermediary in the mevalonate pathway for cholesterol metabolism. Simvastatin, a drug used for hypercholesterolemia treatment, was used as a comparison. The molecular docking results showed that the binding energy values for myricetin, quercetin, dihydromyricetin, kaempferol, quercetin 7,4'-diglucoside, and vitexin were -10.0, -9.4, -9.6, -9.2, -11.4, and -9.9 kcal/mol, respectively. These six flavonoid derivatives from Karamunting fruit have better inhibition scores compared to simvastatin, indicating that these flavonoid derivatives can inhibit cholesterol biosynthesis better than simvastatin and have potential as anticholesterol drugs.